Validation of a Cystic Fibrosis Medication Knowledge Questionnaire - Beverly FitzPatrick PhD; John Hawboldt PharmD; Mary Jane Smith MD; Tiffany Lee PharmD (SAGE Publishing, 2017)
Low adherence to cystic fibrosis (CF) treatment is associated with poor health outcomes, while knowledge of the disease and medication regimen can positively influence adherence. This study's purpose was to develop and validate a questionnaire to help determine CF medication knowledge of pediatric patients and caregivers. Our questionnaire had 37 items: 22 selected-response and 15 open-response questions. We used validation processes from the Standards for Educational and Psychological Testing. CF experts analyzed validity evidence based on content. Then, the questionnaire was field tested with 17 pediatric patients and 18 caregivers. The correlation between age and medication knowledge was medium ( r = .33), but was not significant ( P = .189). Cronbach's α for the overall test was .84. Participants thought the questionnaire was important and suitable, with a few minor suggestions to improve wording. Strong validity evidence indicates the questionnaire could be used to assess medication knowledge and allow more personalized education to improve adherence.